Powder metallurgy for dental biomaterials: Applications, processing, properties and clinical relevance - Moghanian, Amirhossein; Safaee, Sirus; Kizilkurtlu, Ahmet Akif; Mehrdar, Mohammad; Farmani, Ramin; Mehrani, Soroush; Akpek, Ali; Nesabi, Mahdis (ELSEVIER, 2026)
Advances in powder metallurgy (PM) have revolutionized the fabrication of dental biomaterials by enabling precise microstructural control and tailored porosity (up to 80 % porosity in scaffolds) while simultaneously reducing waste and processing time. Although conventional PM processes offer a versatile toolkit for dental applications, consolidation techniques achieve near-full densification (exceeding 85 % of theoretical density) and refine microstructures in metallic and ceramic dental restoratives, resulting in enhanced mechanical integrity (compressive strength up to 203 MPa for TiB2/Ti composites) and biocompatibility. Post-processing treatments, ranging from thermal unbinding and sintering schedules to surface modifications, further optimize the mechanical performance (Young's modulus matching bone at 2.2-12.1 GPa), surface finish, and corrosion resistance of the PM-derived dental components. A diverse array of biomaterials, including titanium-indium alloys for endodontic posts and cobalt-chromium partial denture frameworks, has been successfully produced via PM, demonstrating favorable osseointegration and mechanical performance (tensile strength up to 290 MPa for Ta-Zr alloys). Comprehensive performance evaluations, including fatigue testing, wear analysis, and cytocompatibility assays, confirm the clinical viability of PM-fabricated dental biomaterials. Comparative analyses further elucidate the trade-offs between process parameters, part complexity, and cost efficiency, thereby guiding rational selection for specific prosthetic applications. Nonetheless, challenges persist in scaling PM processes for custom dental geometries, managing the residual porosity (5-15 % in sintered parts), and ensuring consistent biocompatibility across diverse alloy systems. This review aims to cover and analyze these issues by mentioning recent advancements, current limitations, and the future landscape of dental PM-derived biomaterial fabrication in a wide framework.
Keywords: Powder metallurgy; Dental biomaterial; Nano-composite; Bio fabrication; Additive manufacturing; SOL-GEL METHOD; MECHANICAL-PROPERTIES; HYDROXYAPATITE COMPOSITES; TITANIUM; IMPLANTS; ALLOYS; MICROSTRUCTURE; DENSIFICATION; FABRICATION; COATINGS; Materials Science